Exploring the Impact of Work-Life Balance and Self-Efficacy on Work Engagement among Female Employees: The Mediating Role of Job Satisfaction - Puspitawati, Ni Made Dwi; I Komang Oka Permadi; Djuni Henri Taneo; Ni Made Yudhaningsih; I Dewa Nyoman Usadha (Jurnal Aplikasi Manajemen, 2025)
Work engagement for female employees in the hotel industry is a critical issue due to the complexity of balancing demanding work schedules with personal life responsibilities. Achieving work-life balance is essential for maintaining job satisfaction and sustaining high levels of engagement. This study aims to analyze the influence of work-life balance and self-efficacy on work engagement, with job satisfaction as a mediating factor, among female employees in the hospitality sector. This study employed a quantitative approach using a cross-sectional survey design. The population consisted of female employees working at Four-Star Hotels in Bali. A purposive sampling technique was applied to select 106 respondents who met the criteria. Data were collected through structured questionnaires and analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS). The findings reveal that while work-life balance does not directly influence work engagement, it positively affects job satisfaction. Self-efficacy has a positive impact on both job satisfaction and work engagement. Furthermore, job satisfaction acts as a significant mediator strengthening the relationship between work-life balance, self-efficacy, and work engagement. These results suggest that hotel management should implement policies that promote work-life balance to enhance job satisfaction and foster greater work engagement among female employees.